In a day's work : the fight to end sexual violence against America's most vulnerable workers - Yeung, Bernice (New York : New Press, 2020)
"Apple orchards in bucolic Washington State. Office parks in Southern California under cover of night. The home of an elderly man in Miami. These are some of the workplaces where women have suffered brutal sexual assaults and shocking harassment at the hands of their employers, often with little or no official recourse. In this heartrending but ultimately inspiring tale, investigative journalist and Pulitzer Prize finalist Bernice Yeung exposes the epidemic of sexual violence levied against the low-wage workers largely overlooked by #MeToo, and charts their quest for justice. n a Day's Work reveals the underbelly of hidden economies teeming with employers who are in the practice of taking advantage of immigrant women. But it also tells a timely story of resistance, introducing a group of courageous allies who challenge the status quo of violations alongside aggrieved workers--and win." -- Publisher.
"With a new preface from the author"-- Cover.
"First published in the United States by The New Press, New York, 2018."
Keywords: Sexual harassment -- United States; Women foreign workers -- Crimes against -- United States; Women immigrants -- Crimes against -- United States; Sexual abuse victims -- United States; Sex crimes -- United States; Violence in the workplace -- United States; Sex crimes; Sexual abuse victims; Sexual harassment; Violence in the workplace; Women immigrants -- Crimes against; United States; Informational works; Informational works